Preparation and Antioxidant Properties of Germinated Soybean Protein Hydrolysates - Qi, Qianhui; Zhang, Guohua; Wang, Wei; Sadiq, Faizan Ahmed; Zhang, Yu; Li, Xue; Chen, Qihe; Xia, Qile; Wang, Xinquan; Li, Yougui (Frontiers in Nutrition, 2022)
In this study, soybeans during different germination stages were described and compared with regard to morphology, water content, protein, amino acid, and isoflavones. The optimal conditions for the hydrolysis of proteins obtained from germinated soybeans were determined through the response surface methodology. Gel filtration chromatography was used to separate germinated soybean protein hydrolysates after ultrafiltration; whereas, DPPH, ABTS•+, and FRAP assays were used to assess the antioxidant activity of different fractions. Findings of this study revealed that protein and isoflavones contents were high in soybean at 24 h following germination (the bud was about 0.5-1 cm). The proteins from germinated soybeans were hydrolyzed and separated into five fractions G1-G5, and evaluated in terms of their molecular weight and antioxidant activity. Interestingly, the antioxidant activity of germinated soybean protein hydrolysates was found to be higher than other soybean protein hydrolysates derived from soybean meal protein. This suggests that germination can effectively improve the utilization rate of soybean proteins. The antioxidant activity of G3 was best among G1-G5. The results obtained in this study demonstrate that germination for 24 h, when the bud length is about 0.5-1 cm, can be applied as a special pre-treatment of plant seeds in the development of germinated foods. These findings can be used to identify the structure of the potential antioxidative hydrolysates for their possible exploitation in functional foods.